Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

This question already has an answer here:

With $f(x)$ being a real valued function we can write it as a sum of an odd function $m(x)$ and an even function $n(x)$: $f(x)=m(x)+n(x)$

Write an equation for $f(-x)$ in terms of $m(x)$ and $n(x)$:

My attempt using the properties - even function if: $f(x)=f(-x)$ and odd function if: $-f(x)=f(-x)$

$f(x)=m(x)+n(x) \implies f(-x)=m(-x)+n(-x) \implies f(-x)= -m(x)+n(x) \implies f(-x)=n(x)-m(x)$

I think that is correct but then I need to find equations for both $m(x)$ and $n(x)$ in terms of $f(x)$ and $f(-x)$ so a suggestion on how to tackle that would be great.

share|cite|improve this question

marked as duplicate by J. M., Micah, Amzoti, Start wearing purple, Julian Kuelshammer May 30 '13 at 15:46

This question has been asked before and already has an answer. If those answers do not fully address your question, please ask a new question.

up vote 3 down vote accepted


share|cite|improve this answer

Add and subtract $f(x) = m(x) + n(x)$ and $f(-x)=n(x)-m(x)$.

share|cite|improve this answer
sorry but would this be as simple as m(x)= f(x)-n(x) and n(x)=f(-x)+m(x) ? – xiA May 30 '13 at 14:30
No, add the two equations. $m(x)$ will cancel and you can simplify to express $n(x)$ in terms of $f(x)$ and $f(-x)$. Then, subtract to do the same for $m(x)$. – response May 30 '13 at 14:32
Brilliant thanks, It had been a while since I'd used the old elimination method. – xiA May 30 '13 at 14:42

Not the answer you're looking for? Browse other questions tagged or ask your own question.